Consumer intentions to perform difficult behaviors: Role of brand-self connection, prominence and relationship length - Maleeha Shahid Sameeni; Faisal Qadeer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Creation of connections and memory nodes between the brand and self can encourage consumers to engage in relationship sustaining behaviors with the brand. Literature documents the phenomena of interest for rather simple behaviors i.e. purchase (actual or intentions); however, there is lack of systematic study on gauging consumer intentions to perform difficult behaviors (CIPDB) through brand-self connection and brand prominence independently. This paper investigates direct impact of brand-self connection and brand prominence on CIPDB. It also investigates the moderation of relationship length in these two direct relationships and moderation of brand prominence in the selfconnection- CIPDB relationship. The study uses two different product types, identity and instrumental product. The survey includes 297 users of the two product types. The study opens up the new horizon of product-type contingency in studying consumer behavior. Moreover, the findings are helpful for managers to understand how and what level of self-connection and prominence is required for creating necessary consumer intentions to perform difficult behaviors in the favour of the brand, keeping in view the type of product they are dealing in.
Keywords: 330; brand-self connection; brand prominence; relationship length; consumer intentions; self-congruency; difficult behaviors